Diversity of Pods and Beans of Twelve Cocoa Clones (Theobroma cacao L.) in Rainy and Dry Seasons - Adinda Wuriandani; Agung Wahyu Susilo; Suyadi Mitrowiardjo; Bayu Setyawan; Indah Anita Sari (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2018)
Cocoa is a sensitive plant to availability of soil water. The availability of water affects the formation of cocoa pods and beans. The aim of this research was to determine the genetic diversity and the influence of season on the diversity of cocoa beans quality as well as determining the pattern of genotype and season interaction on the quality of physical physiology of cacao beans. The research was conducted in Kaliwining Experimental Station, Indonesian Coffee and Cocoa Research Institute, Jember during dry season (2015) and rainy season (2016). This study used a complete randomized block design 2 x 12 factorial and three replicates as blocks. The first factor was the season consisting of two levels namely, dry season and rainy season. The second factor was cocoa clones, TSH 858, KW 084, KEE 2, Sulawesi 1, Sulawesi 2, BAL 209, KW 215, JTC 5A, JTC 5B, KC 2, KKM 22,and KJ 2. Observation variables included pod diameter, pod length, pod weight, dry bean weight, number of good beans/pod, number of empty beans/pod, numberof beans, and number of pods/tree/season. Data was analyzed using ANOVA fixedfactor. The bean dry weight characteristics possesed a low genetic diversity (0.27%) whereas the physical quality character of other beans, i.e bean count had moderategenetic diversity (14.20%). Meanwhile, the real difference was shown on the dry weight of bean characteristics. The best dry bean weight was observed during the dry season. Clones KW 215 and Sulawesi 1 in the dry season was catego-rized in grade A, while the lowest quality JTC 5A with grade D. The interaction of genotype (clone) with the environment (season) resulted in a significant effect onpod diameter character, pod weight, bean count, dry bean weight, and numberof pods/tree. Based on the biplot AMMI graph it was known that the TSH 858 clone showed genetic stability in bean count character. As for the character ofthe number of pods/tree, clones KKM 22, BAL 209, and KW 084 had the stability of the number of pods in rainy and dry seasons. Clones KJ 2 and Sulawesi 2 showed season-specific in the dry season for the number of pods/tree characters.